Protective IgG titres obtained through vaccination or infection do not protect against canine parvovirus type 2C in dogs - Escobar Pineda, Kenia (2022)
Five cases of dogs with protective IgG antibody titres against canine Parvovirus are describe. The antibody titres were acquired through vaccination or by infection with field strains and that were infected by canine parvovirus in the natural state, developing clinical signs of the disease. Faecal samples from affected dogs were processed using PCR and nested PCR, and amplicons were sequenced for virus genotyping. The results showed that these dogs were infected with canine parvovirus type 2C, indicating that protective IgG antibodies obtained by previous vaccination or infection with field virus were not able to prevent infection or reinfection against canine parvovirus type 2C.